AYURVEDIC MANAGEMENT OF KOSTHASHAKHASHRITA KAMLA W.S.R TO ALCOHOLIC HEPATITIS (ALCOHOLIC LIVER DISEASE) - A CASE REPORT - Jyoti Rani,; Asha Malviya,; R.K Yadava,; VD Agrawal, (International Journal of Ayurveda and Pharma Research, 2020)
Alcoholic hepatitis is an inflammatory condition of the liver. It is caused by excessive alcohol consumption over an extended period of time. Genetics, other liver disorders, and nutrition may also contribute to alcoholic Liver Disease. In Ayurveda there are so many herbs and natural remedies available for treatment of liver diseases. Herein we present a case of married male of age 36yrswho was reported in Kayachikitsa OPD, All India Institute of Ayurveda New Delhi India with chief complaints of pain in abdomen with mild distension, yellowish discolouration of eyes, skin and dark yellow urine, loss of appetite, disturbed sleep, pedal oedema, weakness, anorexia. The diagnosis alcoholic liver disease was made on clinical ground supported with Ultrasonography and blood biochemistry reports. Ayurvedic treatment given was Nitya Virechan with Trivrit Avleha (regular purgative), Bilwadi Gutika Anjana (medicated collyrium) and Shamanoushadhi (palliative drugs). During the treatment the patient was totally abstaining from alcohol. Within 45 days of starting the therapy patient showed significant improvement which were assessed by measuring liver functions through specific clinical features and laboratory parameters. Hence presenting this case is an evidence to demonstrate the effectiveness of Ayurvedic treatment in ALD which can be proved an important guideline for treating Alcoholic Liver Disease with safe and effective Ayurveda line of management.